2004
DOI: 10.1080/09513590400002300
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cholecystokinin secretion and disturbed appetite regulation in women with polycystic ovary syndrome

Abstract: Increased amount of abdominal fat and obesity are common in polycystic ovary syndrome (PCOS). A higher prevalence of bulimia nervosa and greater cravings for sweets have also been reported in these patients. The present study aimed to compare meal-related appetite and secretion of the 'satiety peptide' cholecystokinin (CCK) and glucose regulatory hormones in PCOS women and controls. Sixteen pairs of women with PCOS and controls matched for age and body mass index participated in the study. After an overnight f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 27 publications
1
68
0
1
Order By: Relevance
“…On the other hand, abnormal plasma CCK levels have been characterized in several eating disorders. Basal and postprandial CCK was found to be either increased or decreased in anorectic individuals and reduced in women with polycystic ovary syndrome secretion who tend to binge eat and become overweight (28,207,376). Lack of a CCK response to a high-fat meal was reported to contribute to the hyperphagia-mediated obesity of Prader-Willi subjects (67).…”
Section: Obesitymentioning
confidence: 99%
“…On the other hand, abnormal plasma CCK levels have been characterized in several eating disorders. Basal and postprandial CCK was found to be either increased or decreased in anorectic individuals and reduced in women with polycystic ovary syndrome secretion who tend to binge eat and become overweight (28,207,376). Lack of a CCK response to a high-fat meal was reported to contribute to the hyperphagia-mediated obesity of Prader-Willi subjects (67).…”
Section: Obesitymentioning
confidence: 99%
“…Drummond et al (1998), using a similar methodology to the current study, reported that women in the general population had a mean of 4.4 eating episodes per day (excluding drinks), lower than the eating frequencies for women with PCOS reported here (five eating episodes per day (excluding drinks)). Women with PCOS frequently report food cravings and difficulty losing weight, which may be linked to eating pattern and eating behaviour (Hirschberg et al, 2004;Herriot et al, 2008), perhaps evidenced by the significant negative relationship between BMI and EF, and the weak negative trend between energy intake and EF. The findings from this study highlight a need for future studies designed specifically to investigate the relationship between eating behaviour and BMI in women with PCOS.…”
Section: Recommendation For the Modification Of Dietary Fat Intakementioning
confidence: 99%
“…The effect was dose dependent and specific, i.e. ; it mimicked the satiety induced by food and was not seen with other gut peptides then known [17,30,31,50,51]. The sulphated form of CCK-8 was found to be the most potent for inhibiting food intake [20].…”
Section: Discussionmentioning
confidence: 97%